1998
DOI: 10.1002/(sici)1097-4636(199810)42:1<156::aid-jbm19>3.3.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen adsorption and host tissue responses to plasma functionalized surfaces

Abstract: The physical and chemical characteristics of material surfaces are thought to play important roles in biomaterial-mediated tissue responses. To understand the importance of discrete biomaterial chemical characteristics in modifying host tissue responses, we constructed surfaces bearing different functional groups using radio frequency glow discharge plasma polymerization. Surfaces evaluated included those having high concentrations of −OH, −NH 2 , −CF 3 , and siloxyl groups. These surfaces and polyethylene ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 42 publications
7
66
0
Order By: Relevance
“…26,[37][38][39] Surface topography has been shown to either directly influence the cell response, or indirectly affect the cell responses through the affects they have on the adsorption of proteins. 10,[40][41][42] Cell adhesion results comparing substrates coated with fibronectin, collagen, or no protein revealed that on all protein-coated substrates, there was significantly more cell adhesion on both of the protein-coated substrates compared with the substrates without any protein coating. The results demonstrate that the adsorption of both fibronectin and collagen decreased the contact angle of the substrates, therefore making them more hydrophilic, which is consequently desirable for cell attachment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26,[37][38][39] Surface topography has been shown to either directly influence the cell response, or indirectly affect the cell responses through the affects they have on the adsorption of proteins. 10,[40][41][42] Cell adhesion results comparing substrates coated with fibronectin, collagen, or no protein revealed that on all protein-coated substrates, there was significantly more cell adhesion on both of the protein-coated substrates compared with the substrates without any protein coating. The results demonstrate that the adsorption of both fibronectin and collagen decreased the contact angle of the substrates, therefore making them more hydrophilic, which is consequently desirable for cell attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Keller et al 44 observed ultrahigh-molecular-weight polyethylene surface nanotopography alters the protein orientation and partially aligns single human plasma fibrinogen molecules. Tang et al [40][41][42] have done numerous studies analyzing the cell response to various coating of functional groups on material surfaces. They found subsequent cellular responses were partially mediated by the surface chemistries of the materials due to the functional group coatings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these materials also induced different numbers of total adherent phagocytes depending on the functionality (ANH 2 > ACF 3 > AOH) after short-term implantation, the chronic fibrotic outcome was similar among these different chemistries. 177 In another study, tetrafluoroethylene-hexafluoropropylenecopolymer films were plasma polymerized with tetraglyme to minimize fibrinogen adsorption on the surfaces. However, in vivo studies showed that tetrafluoroethylene-hexafluoropropylene-copolymer films with or without polymerized tetraglyme provoked similar levels of fibrous encapsulation.…”
Section: Effects Of Biomaterials On Macrophage Fusionmentioning
confidence: 99%
“…19 A variety of innovative approaches have been employed to modify solid surfaces in these studies of cell-surface interactions. Examples of techniques employed for this purpose include self-assembled monolayers (SAM's), [14][15][16][17][18][19] photoinitiated grafting, 20 grafting, 11 radio frequency glow discharge (RFGD), also identified as plasma enhanced chemical vapor deposition (PECVD) or plasma polymerization, 3,6,7,12,13,21 and Ar plasma treatment. 22 The present study utilized the RFGD approach to deposit polymeric films containing ACOOH groups, as obtained by the plasma polymerization of vinylacetic acid.…”
Section: Introductionmentioning
confidence: 99%